Evaluation of leachate emissions from municipal solid waste incineration bottom ash and crushed rock used in road construction - Lidelöw, Sofia; Lagerkvist, Anders (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2005)
The use of municipal solid waste incineration (MSWI) bottom ash in road construction may possess a risk to the environment due to the release of e.g. salt and heavy metals. In this study, two years of leachate data from a test road built of MSWI bottom ash and crushed rock in northern Sweden were evaluated. It was found that Cu, Cr, Al, Na, and Cl- were leached in higher amounts from the bottom ash, while the release of Zn, Mg, Ba, and Ca was higher from the crushed rock. The difference between ash and crushed rock leachates decreased over time, mainly due to changes in the ash leachate composition. The road pavement reduced the release rate of most pollutants from the bottom ash compared to the release from the uncovered parts of the road, whereas the release of pollutants from the crushed rock was less affected by the presence of a pavement. Godkänd; 2005; 20070520 (ysko)